LITERATURE REVIEW : PERAN SUPLEMENTASI VITAMIN D DALAM MODULASI IMUN PADA PENDERITA HIV-1 - Chabita, Sarah Aulya; Octaria, Yessi (ARGIPA (Arsip Gizi dan Pangan), 2024)
Human Immunodeficiency Virus (HIV) is a retrovirus that attacks immune cells such as CD4+ cells and macrophages, causing a decline in the immune system that can develop into Acquired Immunodeficiency Syndrome (AIDS). The purpose of this study was to review the role and mechanism of vitamin D supplementation in immune modulation in adults with HIV-1. This study used the literature review method and PICOS to evaluate the effect of vitamin D supplementation on immune modulation in adult HIV-1 patients. Data were collected from PubMed, Elsevier, and Google Scholar databases for the period 2014-2024, using the related search terms “Vitamin D supplementation” or “Cholecalciferol” and “Immune Modulation” or “Immune System” or “Immune” and “Adult” and “HIV-1” and “RCT” or “Randomized Controlled Trial”. Vitamin D supplementation has a positive impact and role in immune modulation, including increased CD4+ T cell counts and markers of immune response. Six relevant articles that met the inclusion criteria were identified and analyzed. Although vitamin D supplementation increases blood levels of vitamin D and aids immune modification, its effect on viral load has not been confirmed. The common dose of vitamin D used in studies ranged from 7.000 IU for 12 months or 12 weeks. Vitamin D supplementation shows potential as an adjunctive therapy for HIV-1, but further trials with larger populations are needed to confirm the optimal dose and long-term effects.